Injectable thermosensitive hydrogel composite with surface-functionalized calcium phosphate as raw materials - Fan RR (Dove Medical Press, 2014)
RangRang Fan,1 XiaoHui Deng,2 LiangXue Zhou,1 Xiang Gao,1 Min Fan,1 YueLong Wang,1 Gang Guo11State Key Laboratory of Biotherapy and Cancer Center, Department of Neurosurgery, West China Hospital, West China Medical School, Sichuan University, Chengdu, 2Department of Human Anatomy, Xinxiang Medical University, Xinxiang, People's Republic of ChinaAbstract: In this study, L-lactide was used to modify the tricalcium phosphate (β-TCP) and tetracalcium phosphate (TTCP) surface which can form functionalized poly(l-lactic acid) (PLLA)-grafted β-TCP (g-β-TCP) and PLLA-grafted TTCP (g-TTCP) particles. The g-β-TCP and g-TTCP obtained were incorporated into a PEG-PCL-PEG (PECE) matrix to prepare injectable thermosensitive hydrogel composites. The morphology of the hydrogel composites showed that the g-β-TCP and g-TTCP particles dispersed homogeneously into the polymer matrix, and each hydrogel composite had a three-dimensional network structure. Rheologic analysis showed that the composite had good thermosensitivity. Changes in calcium concentration and pH in simulated body fluid solutions confirmed the feasibility of surface-functionalized calcium phosphate for controlled release of calcium. All the results indicate that g-β-TCP/PECE and g-TTCP/PECE hydrogels might be a promising protocol for tissue engineering.Keywords: injectable, thermosensitivity, surface functionalization, calcium phosphate, biocompatibility